2020
DOI: 10.1101/2020.04.14.041608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PD-1 Specific ‘Blocking’ Antibodies That Deplete PD-1+ T Cells Present An Inconvenient Variable In Pre-clinical Immunotherapy Experiments

Abstract: Therapeutic antibodies blocking PD-1-/PD-L1 interaction have achieved remarkable clinical success in cancer. In addition to blocking a target molecule, some isotypes of antibodies can activate complement, NK cells or phagocytes, resulting in death of the cell expressing the antibody's target. Human anti-PD-1 therapeutics use antibody isotypes designed to minimize such antibody-dependent lysis. In contrast, anti-PD-1 reagents used in mice are derived from multiple species, with different isotypes, and are not e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Moreover, unlike the majority of therapeutic PD‐1 blockers, which are characterized by a low capacity to interact with Fcγ receptors (FcγRs), such considerations are often not prioritized when designing experiments in mouse models. In this issue of the European Journal of Immunology , Polesso and colleagues report that the use of the PD‐1‐specific antibody (clone) G4 did not show a protective effect in the MCA‐205 mouse sarcoma model, whereas 60% of the animals that were treated with a PD‐L1 antibody rejected the tumor [9]. PD‐1 expression was much higher on tumor‐specific CD8 T cells that resided in the tumor than those in the spleen.…”
Section: Killing Of Pd‐1‐expressing Effector T Cells Mediated By Pd‐1 Blocking Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, unlike the majority of therapeutic PD‐1 blockers, which are characterized by a low capacity to interact with Fcγ receptors (FcγRs), such considerations are often not prioritized when designing experiments in mouse models. In this issue of the European Journal of Immunology , Polesso and colleagues report that the use of the PD‐1‐specific antibody (clone) G4 did not show a protective effect in the MCA‐205 mouse sarcoma model, whereas 60% of the animals that were treated with a PD‐L1 antibody rejected the tumor [9]. PD‐1 expression was much higher on tumor‐specific CD8 T cells that resided in the tumor than those in the spleen.…”
Section: Killing Of Pd‐1‐expressing Effector T Cells Mediated By Pd‐1 Blocking Antibodiesmentioning
confidence: 99%
“…Indeed, Polesso et al. found that RMP1‐14 interacted weakly with PD‐1 + EL4 cells, whereas other PD‐1 antibodies gave much stronger binding signals [9].…”
Section: Killing Of Pd‐1‐expressing Effector T Cells Mediated By Pd‐1 Blocking Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation